Adapting Conservation Policy and Administration to Nonstationary Conditions. Issue 4 (3rd April 2021) - Rissman, Adena R.; Wardropper, Chloe B.
Abstract: False assumptions of stationarity, the idea that natural systems fluctuate within a set and predictable range, are common in conservation policies and public expectations developed since the late 1800s. With examples from United States national forest and water quality policy, we discuss the challenges of nonstationarity for planning and policy. We also raise questions about how resilience is becoming institutionalized. One central problem of managing for resilience is that it does not address the nuances and tradeoffs of managing nonstationary systems, such as keeping some components stable while transforming others. We recommend four paths forward: address root causes of change, increase adaptive capacity, develop science for nonstationarity, and enhance pragmatic flexibility without lowering environmental standards. Dealing effectively with nonstationarity in resource management and science, within our legal and management system of overlapping authorities and capacities, is critical for the intertwined future of people and nature.